Using Personal Qualities Assessment to Measure the Moral Orientation and Personal Qualities of Medical Students in a Non-Western Culture. (June 2013) - Tsou, Kuo-Inn; Lin, Chaou-Shune; Cho, Shu-Ling; Powis, David; Bore, Miles; Munro, Don; Sze, Daniel Man-Yuen; Wu, Hsi-Chin; Hsieh, Ming-Shium; Lin, Chyi-Her
How to select candidates with appropriate personal qualities for medical school is an important issue. This study examined the psychometric properties and group differences of the Personal Qualities Assessment (PQA) to test the feasibility of using it as a tool to assess the medical school applicants in a non-Western culture. Seven hundred forty-six medical students in Taiwan completed two psychometric measures: Mojac to assess moral orientation and NACE to assess four aspects of interpersonal relationships. Thirty-one students completed the tests twice to establish test–retest reliability. A subsample of 127 students also completed a measure of the "Big Five" personality traits to examine the construct validity of these scales. Both Mojac and NACE had acceptable internal consistency and test–retest reliability. Conceptually, coherent and significant relationships were observed between test components and between the NACE and Big Five. NACE but not Mojac varied significantly between different sociodemographic groups. Both tests demonstrated acceptable psychometric properties. However, the predictive validity of PQA requires future studies.